Pengaruh subtitusi tepung pisang raja sereh (Musa paradisiaca L) dan tepung terigu terhadap karakteristik fisikokimia dan organoleptik cookies - utomo, Deny; Maulana, Irfan; Titi Palupi, Hapsari (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2025)
Cookies is one of the popular bakery products in all circles, made from flour but does not require unleavened products through the process of printing and roasting and prioritizing the crispness of its texture with a moisture content that must be less than 5%. Cookies are generally made from wheat flour, flour produced from wheat, dependent on imported wheat needs to be given special attention in efforts to improve alternative food development as a substitution or substitute for flour so as not to always rely on imported flour and be able to utilize local resources. One of the food ingredients that can be used as a substitute for flour is banana flour in making cookies, because the production of bananas is very abundant in Indonesia, but it is still limited in processing. The method used in the research of banana flour and flour cookies is a random design group (shelf) with 5 treatment substitutions and 3 repetitions, so as to get 15 experiments. With the treatment of the ratio of banana flour and flour. Analysis conducted includes physicochemical analysis which includes broken power, water content, ash content, protein content and organoleptic including taste, aroma, color and texture. Statistical analysis was carried out with Analysis of Variance (ANOVA) and Tukey test at a significant level of 95% using Minitab software. The results of the physical research of banana flour cookies and flour produced include broken power analysis ranging from 11.84 - 13.07 N, moisture content 3.11 - 4.14%, ash content 1.18 - 1.77%, levels Protein 10.80% - 12.31%, and organoleptic test of 4.00 - 4.72, aroma 3.24 - 4.12, color 3.32 - 4.20 and texture 3.24 - 4.44. The best research results are found in the treatment of P5 (70% banana flour: 30% flour) with the results of the Physical Test of Texture Analysis (Broken Power) 13.07 N, 3.11% moisture content, ash content 1.77%, protein content 12 , 31%, and organoleptic test of 4.00 (like), aroma 4.12 (like), color 4.20 (like) and texture 4.44 (like).